EDUCATION GAME OF CAR TRANSMISSION BASED ON ANDROID FOR MECHANICAL ENGINEERING COLLEGE STUDENT - Nila Nurlina; Fadelis Sukya; Ahmad Dony Mutiara Bahtiar (Universitas Sultan Ageng Tirtayasa, 2018)
One of the method that can be used in car maintenance is Jishu Hozen that demands the driver to be able not only riding the vehicle but able to maintain it. In order to increase people understanding to Jishu Hozen method especially engineering vocational student we could use Jishu Hozen method to more enjoyable form which is in form of android-based educational game. Game can implemented android application that mostly people and college student has android mobile phone. The purpose of this research focus on to create a method in transmition maintenance using Jizhu Hosen method that implemented android-based game. To fulfil this research purpose we use Information Gathering, designing Jishu Hozen method into android base application to test it. To test the game we spread a questionnaire to 30 engineering college student. The result validity and reliability show that the game is appropriate. The result from questionnaire show that the students’ level of satisfaction upon the game is higher. Besides that, there are differences on students’ knowledge before and after using the education game that tested using paired sample t-test.